FORMULATION AND IN VITRO CHARACTERIZATION OF INTRANASAL MUCOADHESIVE MICROSPHERES OF LAMOTRIGINE USING CHITOSAN BY GLUTERALDEHYDE CROSS LINKING - KAPILESH DAVE; SURESH PUROHIT (International Journal of Pharma and Bio Sciences, 2013)
In the present work attempts were made to deliver lamotrigine; a new antiepileptic drug, via intranasal route as mucoadhesive microspheres, developed by emulsion-solvent evaporation using chitosan as polymer cross linked by Gluteraldehyde by varying stirring rate, viscosity, volume of the phases, drug polymer ratio, and % of cross linking agent. Prepared microspheres were subject to morphological evaluation by SEM, particle size analysis, Drug loading, encapsulation efficiency, % Mucoadhesion, DSC, FTIR measurement, and in vitro drug release study. On the basis of above parameters formulation F30 shows satisfactory properties i.e. smooth spherical shaped microparticles of size range 17 µm to 40 µm with avg. particle size of 23 µm, DSC and FTIR studies support solid solution entrapment with no interaction between drug and other ingredients. Entrapment efficiency was 75.74±0.50 mucoadhesion was 98.5% and drug release was 87.86% which conclude that chitosan based microspheres are suitable for the intranasal delivery of lamotrigine.